THE CONCEPT OF “FREEDOM OF LEARNING” IN A MULTICULTURAL EDUCATION PERSPECTIVE - Sukron Mazid; Sauqi Futaqi; Farikah Farikah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
This paper seeks to examine the concept of “Merdeka Belajar” or “Freedom of Learning” which was initiated by the Indonesian Minister of Education and Culture, Nadiem Makarim. The study of freedom of learning uses text study with content analysis method. The concept of “Freedom of Learning” is very interesting when studied with a multicultural education perspective. Moreover, the two concepts have the same relevance and spirit, namely freedom and justice in the human resources development context, particularly through the educational process. Based on the results, the implementation of “MerdekaBelajar” program so far includes four aspects, namely financing, teachers / educators, assessment, and graduates. In a multicultural perspective, problems in management and assessment aspects basically caused by a misunderstanding of the meaning of standards and standardization. Meanwhile, the teacher and graduate aspects lie in the importance of developing multicultural competencies.Integrating a multicultural education perspective in the “Freedom of Learning” policy also transforms an education system that is creative, innovative, and character.